The mercy [videorecording (DVD)] - Marsh, James, 1963-; Weisz, Rachel, 1970-; Firth, Colin, 1960-; Thewlis, David, 1963- (Screen Media Films, 2019)
Follows the adventures of amateur sailor Donald Crowhurst as he attempts a solo voyage around the world.